Zakat Distribution and Macroeconomic Performance: Empirical Evidence of Indonesia - Muhtadi Ridwan; Laila M. Pimada; Nur asnawi (International Journal of Supply Chain Management, 2019)
Indonesia has a big potential in collecting zakat funds. The demography of Indonesia which has majority Muslim community is a condition that giving big chance to develop and manage this zakat funds. Providing empirical evidence, this study is intended to examine the effects of zakat on macroeconomic performance in Indonesia. The analysis technique of vector auto regression was chosen to show the illustration of the dynamic relationship between each variable. Using a sample of data from 2011-2017, it was found that zakat has a significant positive effect on economic growth. On the other hand, zakat also has a significant positive effect on inflation. The results of this study are expected to be able to stimulate the seriousness of the government and society in maximizing the potential of zakat as an instrument of the economic development of Indonesia.